2021
DOI: 10.1371/journal.pone.0252590
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow derived mast cells injected into the osteoarthritic knee joints of mice induced by sodium monoiodoacetate enhanced spontaneous pain through activation of PAR2 and action of extracellular ATP

Abstract: Conditions that resemble osteoarthritis (OA) were produced by injection of sodium monoiodoacetate (MIA) into the knee joints of mice. Bone marrow derived mast cells (BMMCs) injected into the OA knee joints enhanced spontaneous pain. Since no spontaneous pain was observed when BMMCs were injected into the knee joints of control mice that had not been treated with MIA, BMMCs should be activated within the OA knee joints and release some pain-inducible factors. Protease activated receptor-2 (PAR2) antagonist (FSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…These results indicated that inflammatory mediators were reduced in paw tissues of mice treated with rPPE2. To further demonstrate that PPE2 suppresses formalin-induced tissue inflammation specifically through inhibition of mast cells, we 6 of 21 performed a mast cell transplantation experiment, where bone marrow-derived mast cells (BDMCs) were purified (with > 95% purity, Fig 4A) and injected into the paw of rPPE2-treated mice via subplantar route as described elsewhere (Lee et al, 2002;Patel et al, 2016;Habuchi et al, 2021). When the percentage of inflammation in paw tissue was measured, an increased inflammation was observed in rPPE2-treated mice that were injected with bone marrow-derived mast cells when compared to rPPE2-treated mice that did not receive any mast cells (Fig 4B and C).…”
Section: Rppe2 Subsides Paw Inflammation In Micementioning
confidence: 99%
“…These results indicated that inflammatory mediators were reduced in paw tissues of mice treated with rPPE2. To further demonstrate that PPE2 suppresses formalin-induced tissue inflammation specifically through inhibition of mast cells, we 6 of 21 performed a mast cell transplantation experiment, where bone marrow-derived mast cells (BDMCs) were purified (with > 95% purity, Fig 4A) and injected into the paw of rPPE2-treated mice via subplantar route as described elsewhere (Lee et al, 2002;Patel et al, 2016;Habuchi et al, 2021). When the percentage of inflammation in paw tissue was measured, an increased inflammation was observed in rPPE2-treated mice that were injected with bone marrow-derived mast cells when compared to rPPE2-treated mice that did not receive any mast cells (Fig 4B and C).…”
Section: Rppe2 Subsides Paw Inflammation In Micementioning
confidence: 99%
“…This pain was reduced by a Par2 antagonist. When a Par2 agonist was injected instead of mast cells, the painful phenotype was regained, indicating that Par2 activation in the tissue is mediated by Par2 signaling [ 2 ].…”
Section: Introductionmentioning
confidence: 99%